1999
DOI: 10.1046/j.1365-232x.1999.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging clients' needs for Large Scale Engineering projects

Abstract: In recent years the Large Scale Engineering (LSE) construction sector in Europe has seen profound change. This is mainly due to increasing competitive pressures from the United States and the Asian–Pacific countries which has led in turn to increased pressures to improve competitiveness, productivity and client satisfaction. Lack of understanding of client's requirements hinders achieving such goals especially with the increasing trends of executing LSE projects in a ‘virtual enterprise’ environment. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of the findings from the various workshops and the results of the supplementary studies are reported in other publications ( Hassan et al 1999 ; Male and Mitrovic 1999; Melson and Kronstam 1999; Mitrovic et al . 1999 ; Zantke and Mangels 1999).…”
Section: Approach Adoptedmentioning
confidence: 63%
“…Some of the findings from the various workshops and the results of the supplementary studies are reported in other publications ( Hassan et al 1999 ; Male and Mitrovic 1999; Melson and Kronstam 1999; Mitrovic et al . 1999 ; Zantke and Mangels 1999).…”
Section: Approach Adoptedmentioning
confidence: 63%
“…Electronic exchange of information at the construction stage is rare, paper is undoubtedly the main medium (Building Centre Trust 1999). Similarly, the use of IT as a communication medium between clients and construction organizations remains low (Hassan et al . 1999).…”
Section: Using It In the Construction Sectormentioning
confidence: 99%